The Biology of Lymnaea Stagnalis L. (Gastropoda: Pulmonata) - Sharon Lee Chalfant McDonald (Hello World!, 1969)
Lymnnaea stagnalis is a typical freshwater pulmonate gastropod belonging to the order Basommatophora and the family Lymnaeidae. As a member of the subclass Pulmonata, it is characterized by its detorsion, lack of a ctenidium, hermaphroditism, and transformation of the mantle cavity into a pulmonary cavity, with the concomitant formation of a pneumostome.